The Reconfiguration of China’s Economic Model: The Drive of New Productive Forces and Their Link to International Tensions - Vázquez Rojo, Juan (European Public & Social Innovation Review, 2025)
Introduction: China's economic growth has slowed in the last decade and faces challenges such as demographics, the real estate crisis, and international tensions. Xi Jinping's strategy focuses on the “New Productive Forces” to promote “high-quality growth”, highlighting green technologies and high-tech industries. Methodology: This study examines China's economic transformation and international impact through a longitudinal and descriptive analysis. Results: A reconfiguration is observed with a boost in manufacturing and green technologies, counteracting the decline in the real estate sector, in addition to advances in technological development and an increase in the added value provided through global value chains. However, imbalances persist with weak consumption, high levels of investment, overcapacity, and dependence on exports, especially in manufacturing. Discussion: These imbalances could intensify external tensions with increased sanctions and tariffs. Conclusions: China has made significant progress toward modernizing its economy and developing new technological industries; it faces substantial challenges that could limit its ability to maintain sustainable and balanced growth.